Acute adrenal insufficiency: an aide‐memoire of the critical importance of its recognition and prevention. Issue 3 (March 2016) - Gargya, A.; Chua, E.; Hetherington, J.; Sommer, K.; Cooper, M.
Abstract : Adrenal crisis is a life‐threatening emergency that causes significant excess mortality in patients with adrenal insufficiency. Delayed recognition by medical staff of an impending adrenal crisis and failure to give timely hydrocortisone therapy within the emergency department continue to be commonly encountered, even in metropolitan teaching hospitals. Within the authors' institutions, several cases of poorly handled adrenal crises have occurred over the last 2 years. Anecdotal accounts from members of the Addison's support group suggest that these issues are common in Australia. This manuscript is a timely reminder for clinical staff on the critical importance of the recognition, treatment and prevention of adrenal crisis. The manuscript: (i) outlines a case and the clinical outcome of sub‐optimally managed adrenal crisis, (ii) summarises the clinical features and acute management of adrenal crisis, (iii) provides recommendations on the prevention of adrenal crisis and (iv) provides guidance on the management of 'sick days' in patients with adrenal insufficiency.